The maize golden2 gene defines a novel class of transcriptional regulators in plants. - Rossini, L; Cribb, L; Martin, D; Langdale, J (2001)
In the C4 plant maize, three photosynthetic cell types differentiate: C4 bundle sheath, C4 mesophyll, and C3 mesophyll cells. C3 mesophyll cells represent the ground state, whereas C4 bundle sheath and C4 mesophyll cells are specialized cells that differentiate in response to light-induced positional signals. The Golden2 (G2) gene regulates plastid biogenesis in all photosynthetic cells during the C3 stages of development. However, G2 function is specifically committed to the differentiation of bundle sheath cell chloroplasts in C4 leaf blades. In this article, we report the isolation of G2-like (Glk) genes from maize and rice, providing evidence for a family of Glk genes in plants. The expression profiles of the rice Glk genes suggest that these genes may act redundantly to promote photosynthetic development in this C3 species. In maize, G2 and ZmGlk1 transcripts accumulate primarily in C4 bundle sheath and C4 mesophyll cells, respectively, suggesting a specific role for each gene in C4 differentiation. We show that G2 and ZmGLK1 both can transactivate reporter gene transcription and dimerize in yeast, which supports the idea that these proteins act as transcriptional regulators of cell-type differentiation processes.